Orientation-modulated multiferroic properties of BCZT/LCMO bilayer heterostructures. Issue 3 (15th February 2020) - Hu, Mingzhe; Li, Songbin; Wang, Chuanbin
Abstract: In this paper, orientation-modulated multiferroic properties of Ba0.85 Ca0.15 Zr0.1 Ti0.9 O3 /La0.67 Ca0.33 MnO3 (BCZT/LCMO) bilayer heterostructures grown on (001), (110), and (111)-oriented Nb-doped SrTiO3 single-crystal substrates are investigated. Epitaxially grown heterostructures with sharp and clear interfaces are verified by TEM analysis. Results show the strong orientation dependence of multiferroic properties for the heterostructures. The optimal ferroelectric and dielectric properties lie in the (001) direction, whereas the improved saturation magnetization and piezoelectric response are achieved in (111)-oriented heterostructure. The maximum magnetoelectric coupling is obtained in (111)-oriented heterostructure with a α E31 value of 207 mV/cm·Oe.